The Black Screens of N’Djamena : Video-clubs as a response to the closing of traditional movie theatres in Africa : the case of Chad - (:unkn) unknown (My University, 2013)
This study explores the conditions surrounding the closure of traditional movie theatres inWest Africa, particularly in Chad. It will look at the multi-facetted causes, such as thetechnological, economic, political and financial reasons which have led to the transformationof these cinemas into shops or places of worship.It examines the process of setting up film-viewing alternatives that seem typical of Africa:cultural centers run by church congregations, embassies or the Chadian government andespecially “video-clubs” or “cine-clubs”, informal establishments of cinema distributionfound throughout the African urban landscape.The detailed analysis of these devices as family businesses, social venues and vectors of abastardized form of cinema culture is at the heart of this research. It allows us to identify theeconomic impact of these players as links in the process that takes a movie from itsreproduction in pirated form by Nigerian or Cameroon companies through to screening beforea Chadian audience.Through interviews conducted within a sample of spectators, we have studied their cinemahabits, behaviour and attachment to the films proposed.The latter is the second main axis of this study, particularly concerning the relationship thatthese audiences maintain with Chadian cinema, and, in a broader context, with cinema fictionitself. This thesis lays the foundations for a reflection on the role that the State could play inimproving the conditions of distribution and reception of African cinema throughout Chad
Keywords: African Research